2022
DOI: 10.3390/nu14071469
|View full text |Cite
|
Sign up to set email alerts
|

Protein Energy Wasting in a Cohort of Maintenance Hemodialysis Patients in Dhaka, Bangladesh

Abstract: Malnutrition is associated with high rates of mortality among patients with end stage kidney disease (ESKD). There is a paucity of data from Bangladesh, where around 35,000–40,000 people reach ESKD annually. We assessed protein-energy wasting (PEW) amongst 133 patients at a single hemodialysis setting in Dhaka. Patients were 49% male, age 50 ± 13 years, 62% were on twice-weekly hemodialysis. Anthropometric, biochemical, and laboratory evaluations revealed: BMI 24.1 ± 5.2 kg/m2, mid-arm muscle circumference (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For patients with end-stage renal disease who are undergoing hemodialysis, the complications of anemia, malnutrition, and vascular calcification are considered to increase morbidity and mortality (6)(7)(8), and the underlying mechanisms are inextricably linked to the persistent inflammatory state (9,10). This persistent inflammatory state can also lead to protein-energy wasting, resulting in malnutrition, which is associated with a high risk of mortality in patients undergoing hemodialysis (11,12). Therefore, paying close attention to the inflammatory status of such patients is important.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with end-stage renal disease who are undergoing hemodialysis, the complications of anemia, malnutrition, and vascular calcification are considered to increase morbidity and mortality (6)(7)(8), and the underlying mechanisms are inextricably linked to the persistent inflammatory state (9,10). This persistent inflammatory state can also lead to protein-energy wasting, resulting in malnutrition, which is associated with a high risk of mortality in patients undergoing hemodialysis (11,12). Therefore, paying close attention to the inflammatory status of such patients is important.…”
Section: Introductionmentioning
confidence: 99%
“…HD patients are susceptible to protein energy wasting (PEW), which can result in increased morbidity and mortality [14]. In a single dialysis facility in Dhaka, PEW was estimated to be between 17% and 18% [15,16], while a recent study demonstrated that malnutrition is a common problem in Bangladeshi patients undergoing HD [17]. In addition to PEW, fluid and electrolytes imbalances, mineral bone disorders, anemia due to dialysis, uremia-induced metabolic disruptions compound problems for HD patients [18].…”
Section: Introductionmentioning
confidence: 99%